2008
DOI: 10.1370/afm.816
|View full text |Cite
|
Sign up to set email alerts
|

What Patients Want From Primary Care Consultations: A Discrete Choice Experiment to Identify Patients' Priorities

Abstract: PURPOSEThe consultation is fundamental to the delivery of primary care, but different ways of organizing consultations may lead to different patient experiences in terms of access, continuity, technical quality of care, and communication. Patients' priorities for these different issues need to be understood, but the optimal methods for assessing priorities are unclear. This study used a discrete choice experiment to assess patients' priorities. METHODSWe surveyed patients from 6 family practices in England. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
179
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(200 citation statements)
references
References 34 publications
17
179
2
2
Order By: Relevance
“…Our findings regarding the preferred attributes for choosing a medical practice were consistent with previous DCE studies which identified technical quality of care [26] and doctor communication [27][28][29] as important for choosing a GP appointment. These studies used textual information to represent the service quality attribute levels, unlike the current study which used different representations of quantitative levels.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings regarding the preferred attributes for choosing a medical practice were consistent with previous DCE studies which identified technical quality of care [26] and doctor communication [27][28][29] as important for choosing a GP appointment. These studies used textual information to represent the service quality attribute levels, unlike the current study which used different representations of quantitative levels.…”
Section: Discussionsupporting
confidence: 89%
“…It has also been identified as 'relational'; one of three domains of continuity, the others being 'management' and 'informational'. 11,12 In this study, the GP Patient Survey measure of relational continuity of care was neither related to the three measures of practice telephonesystem efficiency, nor to a proxy measure of receptionist efficiency: namely, the time taken to successfully resolve the appointment request. However, relational continuity was related to appointment availability; practices characterised by the GP Patient Survey as providing less continuity of care experienced increased delays when an appointment with a specific doctor was requested.…”
Section: Discussionmentioning
confidence: 83%
“…It also suggests that continuity of care is desirable so that GP and patient have the opportunity to understand the complexity of the problem over a series of consultations. Continuity of care is highly valued by patients 23 and in the US has been shown to be associated with the confidence felt by primary care physicians in managing MUS. 24 Current policy within UK primary care values access before continuity, meaning that it is now more difficult for people with complex chronic problems to achieve continuity of care with an individual provider.…”
Section: Discussionmentioning
confidence: 99%